Brain in the Peruvian wart (Carrion's disease) - Lastres, Juan B. (1956)
We study in this work, symptoms and syndromes caused by Peruvian Wart (Carrion's Disease) in the brain and its coverings. The clinical picture is varied, presenting symptoms and defined isolated syndromes. Among the former are noted: Fear, disorders of muscle tone, sansitivos, sensory, reflex and mental. Among brain syndromes, the forms: hypertensive, convulsive, pyramidal, extrapyramidal, meningeal, psychic, encephalitic, mixed, asymptomatic lesions of some cranial nerves. Furthermore, core and peripheral locations. Among the brain forms, the most common are the meningo-encephalic and seizure. The pathology has been clarified by Encinas, Mackehenie and Weiss. No injury to endothelium, occlusive thrombosis, tromnboageitis obliterans, gliotic presence of nodules throughout comparable to those observed in the skin. Any vascular area of the brain may be affected, giving as a result the most varied clinical presentations. The nervous tissue is concomitant or subsequent to the alteration of the capillaries. Regarding patogeneze, most of the time these tables are presented in histioide phase without rash (Weiss) or "intercalary period." The (aseptic) degenerative-exudative lesions of brain capillaries, its size and location, are responsible for the various neurological clinical pictures. Although many times the germ is not found, the anatomical lesions are characteristic of verrucous process. Important role played lesions associated with anoxia. The antibiotic treatment gives good results in mild cases. Bartonella bacilliformis is sensitive to all of them (penicillin, streptomycin, aureomycin, chloromycetin, terramycin, iloticina) and their use allows to control the infection and improve bartonelósica pari passu nervous picture, when injuries are not very extensive and vital organs. Should be added to the therapeutic, vitamins B1 and B12 and liver extract.